ANALISIS BEST PRACTICE PENGEMBANGAN DESA WISATA LEREP KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Vita Afrilisa; Maesaroh Maesaroh (Journal of Management and Public Policy, 2026)
Village development is a strategic component in realizing community welfare and achieving the Sustainable Development Goals (SDGs), particularly in poverty alleviation and local economic development. One way to achieve this is through the development of tourism villages. Lerep Tourism Village, West Ungaran District, Semarang Regency, is a tourism village that has successfully been classified as an advanced tourism village and has received various awards at the regional and national levels. This study aims to analyze best practices in the development of Lerep Tourism Village and supporting factors for tourism development. This study uses a descriptive qualitative method with data collection techniques through interviews, participatory observation, and documentation. The research analysis refers to the concept of best practices according to Prasojo which includes impact, partnership, sustainability, leadership, and transferability, as well as supporting factors for tourism according to Cooper, namely attractions, accessibility, amenities, and supporting services. The results of the study indicate that the development of Lerep Tourism Village has met the criteria of best practices through economic and social impacts, internal and external partnerships, continuous innovation, visionary leadership, and knowledge transfer activities to other regions. Supporting factors for tourism include the diversity of tourism products, ease of access, availability of supporting facilities, and professionally managed tourism services, although there are still problems in optimizing the role of Pokdarwis at the hamlet level. As a suggestion, it is necessary to strengthen Pokdarwis institutions at the hamlet level and prepare tourism village management documents as development guidelines and references for other tourism villages.